Geographical competition-complementarity relationships between Greek regional economies - Yiannis Kamarianakis; Vagelis Kaslis (European Regional Science Association (ERSA), 2005)
This paper examines the nature of interregional competition and complementarity in Greece. Covering the 1975-2002 period, the analysis provides a picture of the interregional interactions by focusing on derived linkages between the regional economies. The adopted methodology combines previous approaches based on the Dendrinos-Sonis model (e.g. Nazara et al 2002, Bonet 2003) and a cointegration modeling framework (Marquez and Hewings, 2003). A sensitivity analysis of the model coefficients that designate competition or complementarity, with respect to time, is undertaken as well.
Keywords: 330